Insights into the hydrated electron generation from UV/aniline: Mechanism and quantum efficiency. (January 2022) - Yu, Xiaoping; Tan, Ling; Yu, Yalin; Xia, Yun; Guan, Zhen; Gu, Jia; Wang, Jing; Chen, Huan; Jiang, Fang
Abstract: The insight into the neglected reduction process accompanied by UV-based oxidation process may provide new ideas for the development of advanced oxidation and reduction technologies. In this study, aniline was comprehensively investigated as an unexpected indicator of hydrated electron (eaq − ) under UV irradiation. Monochloroacetic acid (MCAA) was selected as the probe of eaq − and the balance of chloride ions indicated the reduction of MCAA. Further, laser flash photolysis experiments demonstrated the generation of eaq − in the UV/aniline process and the half-life period of formed eaq − was demonstrated to be 0.13 μs. The photolysis of aniline along with the decay of the excited state of aniline was responsible for the eaq − generation. Besides, the hydrogen atom (H) generated from the photolysis can subsequently reacted with OH − to generate eaq − . The photolysis pathways of aniline were proposed by the results of GC-MS. Aniline was abstracted of H in solution to the formation of aniline radical (PhNH) or form aminophenol in three different isomers (orto-, meta- and para-aminophenol). Moreover, UV/aniline showed a higher reducing capacity of MCAA compared with other organic electron donors and sustained a highly reducing ability in a wide pH. And the calculation results of quantum efficiency (Φ) showed that excessive aniline was not conducive to the elevation of Φ. This study introduced a novel pathway of eaq − generation during the photolysis of aniline and provided a new perspective for eaq − -based advanced reduction processes. Graphical abstract: Image 1 Highlights: Highly reductive eaq − was generated in the UV/aniline process. The photolysis of aniline along with the decay of the excited state of aniline was responsible for the eaq − generation. The excessive aniline was not conducive to the elevation of Φ (quantum efficiency). UV/aniline process showed high reduction ability in MCAA reduction in a wide range of pH.